Study on feeding effect of dietary protein sources of on blood or milk urea nitrogen in native cows (Bangladesh Journal of Livestock Research, 2016)
A feeding trial with 30 Pabna milking cows of 2 to 4 parities dividing equally into 5 groups was conducted to determine the effect of feeding protein from different sources on blood or milk urea nitrogen, and milk yield or protein content in native cows. Considering a group of cows fed a diet of rice straw and concentrate as the control (T0), two out of the rests were fed either with urea-molasses straw (UMS) (T1) or Matikalai (Vigna mungo) hay ( T2) as sources of basal roughage. The rest two groups of cows were fed the control diet replacing percent (%) of feed protein by the amount of urea and molasses fed to UMS group. The amount of urea and molasses was fed daily either in two meals (T3) or fed to cows mixing with other concentrate feed (T4). Feeding a basal diet of UMS, DS or leguminous hay did not affect milk protein (%) and daily milk production Feeding urea and molasses in meals or mix (T3 and T4) did not affect significantly (p>0.05) BSU and MUN contents. It indicates that feeding urea and molasses in two meals in a day either as a single mix of the two or as a mix of the two with concentrates significantly (p>0.05) reduced the concentration of BSU or MUN without having any change in milk protein (%) of the cows. Dry matter (DM) intake was significantly (p